Endophytic Consortium With Diverse Gene-Regulating Capabilities of Benzylisoquinoline Alkaloids Biosynthetic Pathway Can Enhance Endogenous Morphine Biosynthesis in Papaver somniferum - Ray, Tania; Pandey, Shiv S.; Pandey, Alok; Srivastava, Madhumita; Shanker, Karuna; Kalra, Alok (Frontiers in Microbiology, 2019)
Secondary metabolite biosynthesis in medicinal plants is multi-step cascade known to be modulated by associated endophytes. While a single endophyte is not able to upregulate all biosynthetic steps, limiting maximum yield achievement. Therefore to compliment the deficient characteristics in an endophyte we tried consortium of endophytes to achieve maximum yield. Here, efforts were made to maximize the in planta morphine yield, using consortium of two endophytes; SM1B (Acinetobacter sp.) upregulating most of the genes of morphine biosynthesis except T6ODM and CODM, and SM3B (Marmoricola sp.) upregulating T6ODM and CODM in alkaloid-less Papaver somniferum cv. Sujata. Consortium-inoculation significantly increased morphine and thebaine content, and also increased the photosynthetic efficiency of poppy plants resulted in increased biomass, capsule weight, and seed yields compared to single-inoculation. The increment in morphine content was due to the modulation of metabolic-flow of key intermediates including reticuline and thebaine, via upregulating pertinent biosynthetic genes and enhanced expression of COR, key gene for morphine biosynthesis. This is the first report demonstrating the endophytic-consortium complimenting the functional deficiency of one endophyte by another for upregulating multiple genes of a metabolic pathway similar to transgenics (overexpressing multiple genes) for obtaining enhanced yield of pharmaceutically important metabolites.